Perancangan Clinical Information System (CIS) Pada Instalasi Rawat Jalan di Rumah Sakit ABC - Desi Pibriana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
The development of technology has increased rapidly in the past few years encourage the needed for rapid information delivery in service activity in many section. During this time, the entire process in ABC Hospital, starting from the process of registration of the new patients, registration for treatment to the clinic, examination, further examination in the laboratory, the payment of medicine and hospital service are still written on paper or card. As a result, Hospital employee have to take a long time to access the data. In addition, today ABC Hospital have to face operational costs such as printing cards and purchasing shelves for data storage, frequent data loss and redudancy, and inefficiency in reporting process for management of the ABC Hospital. Therefore, the purpose of ths study is to design a Clinical Information System(CIS) in a website based with the PHP programming language and MySQL as a database. This Information system is designed using a FAST (Framework for the Application of Systems Thinking) methodology. The result of this study is a Clinical Information System design complete with a user interface that is ready to be built to help ABC Hospital Employee in outpatient service so that patient can receive more quickly, precisely and accurately service.